Stable isotopes in a stalagmite from NW Sweden document environmental changes over the past 4000 years - Sundqvist, Hanna; Holmgren, Karin; Moberg, Anders; Spötl, Christoph; Mangini, Augusto (Boreas, 2010)
Sundqvist, H. S., Holmgren, K., Moberg, A., Spötl, C. & Mangini, A. 2009: Stable isotopes in a stalagmite from NW Sweden document environmental changes over the past 4000 years. Boreas, 10.1111/j.1502-3885.2009.00099.x. ISSN 0300-9483. This study of a 4000-year-old stalagmite from Korallgrottan in northwestern Sweden highlights the potentials and challenges when using stable isotopes in stalagmites as climate proxies, as well as the fact that the relationship between climate and proxy may change through time. Both the oxygen and the carbon isotopes display an overall trend of enrichment together with decreasing growth rates over the time period covered by the stalagmite, which is considered a generally cooling period according to current palaeoclimate understanding. The stable isotope records show enriched isotopic values during the, for Scandinavia, comparatively cold period AD 1300-1700 and depleted values during the warmer period AD 800-1000. The indication of a negative relationship between measured δ18O and surface temperature concurs with earlier reported stalagmite records from regions with a seasonal snow cover and is further supported by the fact that the stalagmite δ18O record shows general similarities with both regional and hemispheric temperature reconstructions available for the past 500 and 2000 years, respectively. Compared with a stable isotope record of lacustrine carbonates from northern Sweden, however, shifting correlations over time between the two records indicate that a local hydrological change may have taken place at Korallgrottan, or at the lake, compared with around 1000 years ago. The earlier part of the stalagmite δ18O might thus be influenced, to some extent, by another process than the later part, which means that a negative relationship between δ18O and surface temperature might not hold for the entire 4000-year-old record.
Erstmals am 22 December 2009 online veröffentlicht
Gesehen am 06.09.2023